Pendidikan Karakter Dalam Perspektif Surat Al-An'am Ayat 151-153 - Ricki Yakup; Waharjani Waharjani (Oasis : Jurnal Ilmiah Kajian Islam, 2024)
The reality of the crisis of aqidah and morals in Indonesia today still seems so alarming and it seems that the phenomena that occur in human life today are far from the basic values of Islam, namely the Qur'an and Hadith. As a result, deviations occur in the community. This study aims to 1) find out the opinion of the commentators regarding the QS. Al-An'am verses 151-153, 2) find the essence contained in the QS. Al-An'am verses 151-153, 3) find the educational implications contained in the QS. Al-An'am verses 151-153 about the morals of the easy way towards efforts to build aqidah and morals. The approach used in this research is a qualitative approach, while the method used is descriptive analysis method with the type of library research, namely by collecting data that is related to the researcher's discussion. Based on the results of this research analysis shows that the essence of QS. Al-An'am verses 151-153, 1) the importance of Aqidah for a Muslim in order to avoid deviant teachings, 2) a Muslim must have a good morality in fostering aqidah and morals, 3) Muslims are obliged to avoid deviant teachings of the Islamic religion. Educational Implications of QS. Al-An'am verses 151-153 namely: 1) stay away from polytheism to Allah, 2) do good to both parents, 3) protect children, 4) avoid evil deeds, 5) protect the soul, 6) love orphans, 7) perfecting measures and scales, 8) fair in speech and action, 9) keeping promises, 10) and being obedient and obedient to the rules. Efforts in fostering Aqidah and Morals are carried out by several methods, namely the first method, the exemplary method, the habituation method, the advice method, the story method, the Ibrah method, and the educating method.